Cytotoxicity of α-mangostin encapsulated polymeric nanoparticles against lung cancer cells - Mai Phuong, Nguyen Thi; Lam, Tran Dai; Mai, Ta Thu; Hop, Nguyen Trung (Academia Journal of Biology, 2018)
Alpha-Mangostin (AMG) isolated from Garcinia mangostana L., has been intensively reported to possess potent anti-cancer properties. However its clinical application is limited due to poor aqueous-solubility. Here, we successfully synthesised and characterised water-soluble ß-cyclodextrin-coated AMG (NMG) with size of